Immune and hematologicak responses to the third dose of an mRNA COVID-19 vaccine: a six-month longitudinal study - Bawazir, Waleed M.; Ibad, Ahmad Al; Mohsin, Muneeba; Niyazi, Hanouf A.; Alamri, Turki A.; Bazuhair, Mohammed A.; Hazzazi, Mohannad; Chehab, Noura A.; Harakeh, Steve; Yousafzai, Yasar Mehmood (Frontiers in Cellular and Infection Microbiology, 2025)
The deployment of mRNA vaccines against SARS-CoV-2 is a major landmark in controlling the COVID-19 pandemic. However, the activation of adaptive immunity and its longevity after a booster dose warrant further investigation. Moreover, the interplay between inflammation and immune thrombosis after transfection needs further insights that could help examine the vaccine’s potential for adverse events following immunization (AEFIs). This study investigates the biochemical and hematological responses to the third dose of a COVID-19 mRNA vaccine in 68 healthy participants who had previously received two doses of the vaccine. Blood samples were collected at baseline (before vaccine dose; D0), 48 hours post-vaccination (D2), and then at days 30, 60, 120, and 180 (D30, D60, D120, D180). The study focused on analyzing changes in anti-SARS-COV-2 immunoglobulins (IgG and IgA), inflammatory biomarkers (IL-6, IFN-γ, CRP, hs-CRP), coagulation factors (PT, APTT, D-dimers), and blood cell counts (neutrophils, leukocytes, platelets) at D2 post-vaccination, and IgG and IgA at days 2, 30, 60, 120, and 180 post-vaccination. In this study, no clinical AEFIs were observed in any of the recipients. Slight changes were observed in the levels of inflammatory and coagulation biomarkers, and blood cells. Levels of CRP and hs-CRP increased slightly but significantly, d-dimers were raised, and PT and aPTT were prolonged significantly. A small but significant decrease was observed in IFN-γ and mean lymphocyte counts, whereas no change was observed in the levels of IL-6, neutrophils, and platelet count at D2. Levels of IgG and IgA showed sustained increase over the six-month period. These results collectively demonstrate that the third dose of the mRNA vaccine elicits a rapid and sustained immune response characterized by increased IgG and IgA levels. The changes observed in inflammatory markers and coagulation factors after vaccination observed shortly after vaccination require further investigations.